Revisiting alkaline cupric oxide oxidation method for lignin structural analysis - Yang, Guangxu; Gong, Zhenggang; Luo, Xiaolin; Shuai, Li (Frontiers in Bioengineering and Biotechnology, 2022)
Lignin structural analysis is important for the comprehensive utilization of lignin as well as delignification and bleaching during pulping while it is difficult to completely elucidate lignin structure due to its structural complexity and heterogeneity. Depolymerization of lignin into simple monomers via alkaline cupric oxide oxidation (OxCuO) followed by chromatographic analysis of the monomers is an effective method for lignin structural analysis. Here we revisited the OxCuO of lignin model compounds (monomers and dimers) and three representative lignocelluloses (i.e., Eucalyptus, Masson pine, and corn stover) to understand the effects of reaction conditions and lignin sub-structures on oxidation product yields and distributions. The improved OxCuO was found to be effective in oxidatively breaking the robust interunit C-C bonds in the - and -5 moieties of lignin other than β-O-4 linkages at an elevated temperature (210 C). Further degradation of the monomeric oxidation products could also occur to reduce the monomer yields under a severe condition (i.e., high temperature and long reaction time). In addition, O2 inputs could reduce the monomer yields via nonselective overoxidation, thus having negative effects on accurate structural analysis of lignin. The O2 removal via ultrasonication combined with N2 flushing prior to the oxidation reaction could improve the monomer yield about 1.2 times (compared to that without O2 removal) at a low biomass loading of 5 wt%. By using the improved method of OxCuO, a monomer yield of 71.9% could be achieved from Eucalyptus (hardwood) lignin, which was much higher than conventional nitrobenzene oxidation (59.8%) and reductive depolymerization (51.9%). Considering the low cost, high availability, and low toxicity of CuO, the improved OxCuO could be a convenient and economic method for more accurate lignin structural analysis.